Evaluation of GSMaP Rainfall Data in the Aceh Region - Sahlan, Muhammad; Ilhamsyah, Yopi; Fadli, Muhammad; Masrurah, Zakia (Journal of Climate Change Society, 2024)
Rainfall measurement data in the field is quite limited, however, satellite data obtained by remote sensing methods are widely available. However, its accuracy must still be tested using observational rainfall data. The objective of this research was to validate GSMaP satellite estimated rainfall data with Automatic Rain Gauge (ARG) rainfall data at rain stations dispersed over Aceh Province's west-central region, as well as to identify the primary drivers for GSMaP data error. ARG and GSMaP data sources. A comparison of GSMaP data accuracy using a combination of Pearson and RMSE tests shows that GSMaP performance is very low in the dry and transition seasons and significantly better in the rainy season. GSMaP, on the other hand, is still unable to offer sufficient precise rainfall estimation data for each season. Meanwhile, a comparison by elevation shows that GSMaP data is not fully reliable.